2011
DOI: 10.5194/bg-8-1595-2011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide fluxes over an ancient broadleaved deciduous woodland in southern England

Abstract: Abstract.We present results from a study of canopyatmosphere fluxes of carbon dioxide from 2007 to 2009 above a site in Wytham Woods, an ancient temperate broadleaved deciduous forest in southern England. Gapfilled net ecosystem exchange (NEE) data were partitioned into gross primary productivity (GPP) and ecosystem respiration (R e ) and analysed on daily, monthly and annual timescales. Over the continuous 24 month study period annual GPP was estimated to be 21.1 Mg C ha −1 yr −1 and R e to be 19.8 Mg C ha −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 65 publications
8
33
0
Order By: Relevance
“…Removal of such data caused a data gap of around 23%. There is no universal method to account for advection [33] and our method is in agreement with the several authors recording such errors using open path systems [26,32,34].…”
Section: Removal Of Negative Nighttime Co 2 Fluxessupporting
confidence: 86%
See 2 more Smart Citations
“…Removal of such data caused a data gap of around 23%. There is no universal method to account for advection [33] and our method is in agreement with the several authors recording such errors using open path systems [26,32,34].…”
Section: Removal Of Negative Nighttime Co 2 Fluxessupporting
confidence: 86%
“…The corrected data is then gap-filled and partitioned into gross primary productivity (GPP) and ecosystem respiration (Re). The secondary data processing methodology used is similar to the proposed corrections by Thomas et al [32].…”
Section: Secondary Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another R s component sampling study on clay-rich soils (Moyano et al, 2008) showed similar R r (∼45 %) but lower R m (∼5 %), possibly reflecting differences in seasonal dynamics between forests and methods. The mean annual C budget (Table 3) of this temperate deciduous oak forest of ∼1700 and ∼700 g C m −2 yr −1 for GPP and NPP, respectively, is similar to other studies in the UK (Thomas et al, 2011), Europe (Hibbard et al, 2005) and globally (Melillo et al, 1993;Luyssaert et al, 2007), and for ECM dominated forests (Vargas et al, 2010b). However, our data set enabled us to fully account for the R a component of R s (i.e.…”
Section: Soil Respiration Component Fluxes and The Forest C Budgetsupporting
confidence: 80%
“…These results suggest that vegetated suburban areas are able to support high rates of evapotranspiration (≈ 3 mm day −1 ). For comparison, summertime daily evapotranspiration rates from UK woodlands are around 4-5 mm day −1 (Roberts et al, 2005;Thomas et al, 2011). Evapotranspiration rates from residential and recreational areas in suburban MinneapolisSaint Paul, Minnesota are around 3 mm day −1 in summer (Peters et al, 2011), comparable to the BLS-MWS results shown here, but near zero in winter (conditions are much colder and drier).…”
Section: Comparison With Other Sitessupporting
confidence: 72%